With a Little Help from Nurseries - Childcare Services and Mothers' Employment in Italy - Chiara Puccioni; Daniela Vuri (CESifo GmbH, 2025)
This study evaluates the impact of an Italian government initiative launched in 2007, which allocated exteuro1 billion to regional governments to enhance early childhood care services for children aged 0-2, targeting both public and private childcare options. Exploiting variations in the timing of implementation across regions, we assess the program's effectiveness in increasing the public provision of early childcare services and maternal labor market participation. Results show a significant increase in both public childcare slots and labor market participation among mothers. However, the initiative had limited effects on less-educated women, likely due to the service's relatively high costs, which may hinder broader accessibility.
Keywords: C21; C22; H52; H75; J13; J22; 330; early childcare services; mothers' labor supply; staggered difference-in-difference; dynamic estimates